Gender Mediation in Ethical Perceptions: Traits, Money, Religiosity - Agustina, Eura Kurnia; Hermawan, Sigit (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the impact of Machiavellian traits, love of money, and religiosity on ethical perceptions among accounting students, utilizing a quantitative approach. Employing simple random sampling, data were collected from 155 respondents at Muhammadiyah University of Sidoarjo. SmartPLS version 3 software was employed for data analysis. The findings reveal that Machiavellian traits, love of money, and religiosity significantly influence students' ethical perceptions, with gender acting as an intervening variable. This study underscores the individual variability in Machiavellian traits, love of money, and religiosity, emphasizing their nuanced role in shaping ethical behavior among students. The implications suggest that students who prioritize ethical conduct in all circumstances may be less susceptible to external influencing factors. Highlights: The study explores the influence of Machiavellian traits, love of money, and religiosity on students' ethical perceptions. Gender is examined as a mediating variable in the relationship between these traits and ethical perceptions. Individual variations in these traits are emphasized, with implications for ethical behavior among students. Keywords: Machiavellian traits, Love of money, Religiosity, Ethical perceptions, Gender mediation